Comparison of Mean Onset and mean duration of action between Atracurium and Cisatrcurium in patients undergoing Elective Surgery - Haleema Tahir, Syed Sajjad Raza Kazmi, Sabir Khan, Zulqarnain Butt, Tahir Nazir, Hafiz Wajih-Ul-Hassan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Neuromuscular monitoring is required in an anesthetized patient to ensure complete recovery from a neuromuscular blockade. Cisatracurium and atracurium are used in adult patients undergoing diagnostic and surgical procedures with general anesthesia. Objective: To compare the mean onset time and mean duration of action between atracurium and cisatracurium in patients undergoing elective surgery. Methodology: This randomized control trial was conducted in the Department of Anesthesia/ICU at Jinnah Hospital Lahore from March 10, 2022, to September 10, 2022. A total of 68 patients were enrolled with 34 patients assigned to each of the two groups. Participants were randomly selected to receive either atracurium (Group A) or cisatracurium (Group B). On completion of the surgery, patients were reversed with injection neostigmine 0.05 mg/kg and 0.4 mg glycopyrrolate. Mean onset time and duration of action were noted. Results: The mean onset time of the patients in Group A was 3.94±1.52 minutes and in Group B the mean onset time of the patients was 2.50±1.18 minutes (p=<0.001). In the atracurium group, the mean duration of action of the patients was 34.94±3.06 minutes, and in the cisatracurium group, the mean duration of action of the patients was 58.97±7,25 minutes (p-value=<0.001). Conclusion: The cisatracurium group has significantly shorter mean onset time and longer mean duration of action as compared to the atracurium group in patients undergoing elective surgery Keywords: Anesthesia, Atracurium, Cisatracurium, Duration of action, Onset time.